Analisis Yuridis Perlindungan Nasabah Bank Dalam Tindak Pidana Pencurian Data Melalui UU ITE dan UU Perbankan - Abdullah, Nayla Putri; Yadila, Natasya; Amelia, Sabina Putri; Widiastiwi, Alisha Reva; Camilla, Garneta Rizka (Media Hukum Indonesia (MHI), 2024)
This study discusses the issue of personal data protection in the Indonesian banking sector, which is becoming increasingly important as digital technology advances and cybercrime threats increase. The study was conducted using a normative legal analysis method, which includes a review of literature, regulations, and policies, such as the ITE Law and the Banking Law. The results of the study indicate that, although there are regulations, such as the ITE Law, the Banking Law, and POJK, their implementation is considered ineffective. One of the relevant regulations is Article 26 paragraph (1) of the ITE Law, which stipulates that the use of personal data in electronic media must obtain the consent of the data owner, and violations of this provision can result in civil lawsuits. In addition, banks are required to maintain the confidentiality of customer information in accordance with adequate security standards, as stipulated in Article 47 paragraph (2) of Law No. 10 of 1998 concerning Banking. This regulation is equipped with strict sanctions in the form of fines of up to IDR 1 billion or imprisonment of up to 8 years for perpetrators of violations. The main problems include the low level of compliance of financial institutions with security standards, the lack of digital literacy of the community, and technical challenges in supervision and law enforcement.